I-Semiprime Submodules - Abdul-AlKhalik, Adwia J. (Iraqi Journal of Science, 2019)
Let be a commutative ring with identity and a fixed ideal of and be an unitary -module.We say that a proper submodule of is -semi prime submodule if with . In this paper, we investigate some properties of this class of submodules. Also, some characterizations of -semiprime submodules will be given, and we show that under some assumptions -semiprime submodules and semiprime submodules are coincided.